2008
DOI: 10.1002/cphc.200700758
|View full text |Cite
|
Sign up to set email alerts
|

Development of In Situ Electrochemical Scanning Electron Microscopy with Ionic Liquids as Electrolytes

Abstract: We report that ionic liquids (ILs) can be observed by electron microscopy without any charging of the liquid. Based on this, we present an in situ electrochemical scanning electron microscopy (in situ ECSEM) system. The key technology that enables in situ ECSEM is that charges can be removed from an IL by grounding it with a Pt wire, even if the IL is in an insulating glass cell. As a first demonstration, we describe the redox reaction of a polypyrrole (PPy) film accompanied by changes in its thickness when it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 45 publications
(38 reference statements)
0
55
0
Order By: Relevance
“…These polymers physically deform when they undergo an oxidation/reduction cycle in an electrolyte solution because of doping/dedoping of cations in the PILE. Ding et al [251] and Arimoto et al [252] have succeeded to reveal the mechanism by the use of electrochemical techniques and an in situ electrochemical SEM system with energy-dispersive X-ray fluorescence spectroscopy (EDX), respectively. A PANI-based soft actuator device shows fast switching speed in BuMeImBF 4 and showed no failure after 1 million cycles under ambient conditions.…”
Section: Redox Devicesmentioning
confidence: 99%
See 2 more Smart Citations
“…These polymers physically deform when they undergo an oxidation/reduction cycle in an electrolyte solution because of doping/dedoping of cations in the PILE. Ding et al [251] and Arimoto et al [252] have succeeded to reveal the mechanism by the use of electrochemical techniques and an in situ electrochemical SEM system with energy-dispersive X-ray fluorescence spectroscopy (EDX), respectively. A PANI-based soft actuator device shows fast switching speed in BuMeImBF 4 and showed no failure after 1 million cycles under ambient conditions.…”
Section: Redox Devicesmentioning
confidence: 99%
“…[289] A possibility of in situ observation of chemical reactions in ILs with an electron microscope was reported by our group. [252,290] The first example was a PPy film deposited on a Pt electrode (PPy j Pt electrode), redox of which is accompanied by changes in film thickness due to doping and dedoping of electrolyte ions. This electrode and a counter electrode were immersed in BuMeImTf 2 N and the cell was set in a vacuum chamber of an SEM so as to observe the cross-section of the PPy film.…”
Section: Electron Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…If this is correct, it is possible to observe the reactions by an electron microscope. 13,14 We attempted to prove this possibility with SEM observation of electrochemical Ag deposition. For this purpose, we designed an electrochemical cell having a specific figure, as shown in Fig.…”
Section: Observation Of Electrochemical Reactionsmentioning
confidence: 99%
“…The low vapor pressure of ILs allows their characterization [3] and processing [4,5] using high-vacuum techniques. In our previous works, we developed a new deposition technique of ILs in vacuum using a continuous-wave infrared (CW-IR) laser to prepare nanoscale IL droplets and thin films on a substrate without any decomposition [6], and also demonstrated that IL nanodroplets can be used as microreactors for crystal growth in vacuum [7].…”
Section: Introductionmentioning
confidence: 99%